The students-as-partner experience: Perspectives from the students and the faculty - Millar, Nathan; Scarff, Bria; Kostouros, Patricia (International Journal for Students as Partners, 2024)
This article offers a case study of a student-faculty partnership. Focusing on the perspectives of two student research assistants and a faculty member, the authors utilize current literature on student-faculty partnerships to support their perspectives. This case study adds to the body of research suggesting student-faculty partnerships enrich and mutually benefit those involved. This article explores the working partnership of the consultation team and their work as part of a large collaborative project amongst post-secondary institutions and community-based organizations. Over the course of 3 years, success was evidenced by the outcomes of this project. The team has led workshops on the subject matter, and, additionally, contributed to the co-creation of a workbook/e-course on mitigating vicarious trauma for English language learning teachers. The research team published two subject-related articles. This article explores the facets that impacted the quality of the partnership.